Advances in Unit Testing: Theory and Practice - Xie, Tao; Tillmann, Nikolai; Lakshman, Pratap (Proc. 38th International Conference on Software Engineering (ICSE 2016), 2016)
Parameterized unit testing, recent advances in unit testing, is a new methodology extending the previous industry practice based on traditional unit tests without parameters. A parameterized unit test (PUT) is simply a test method that takes parameters, calls the code under test, and states assertions. Parameterized unit testing allows the separation of two testing concerns or tasks: the specification of external, black-box behavior (i.e., assertions or specifications) by developers and the generation and selection of internal, whitebox test inputs (i.e., high-code-covering test inputs) by tools. PUTs have been supported by various testing frameworks. Various open source and industrial testing tools also exist to generate test inputs for PUTs. This technical briefing presents latest research on principles and techniques, as well as practical considerations to apply parameterized unit testing on real-world programs, highlighting success stories, research and education achievements, and future research directions in developer testing.